Interior of Catholic Cathedral, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (The Catholic Truth Agency, 2010)
Photograph of the interior of the Cathedral of the Immaculate Conception, a Roman Catholic Cathedral in Port of Spain, Trinidad and Tobago with a foundation stone laid in 1816, and which was completed and consecrated in 1851. Posted January 5, 1908 from New York with U.S. 1 cent stamp.
Colour: White, Green, Grey and Cream Hues; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Catholic Church--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago; Interior architecture--Trinidad and Tobago; 1908; Stained glass windows--Trinidad and Tobago; Columns--Trinidad and Tobago; Cathedrals--Trinidad and Tobago